The Role of Antifungals against Candida Biofilm in Catheter-Related Candidemia - Emilio Bouza; Jesús Guinea; María Guembe (MDPI AG, 2014)
Catheter-related bloodstream infection (C-RBSI) is one of the most frequent nosocomial infections. It is associated with high rates of morbidity and mortality. Candida spp. is the third most common cause of C-RBSI after coagulase-negative staphylococci and Staphylococcus aureus and is responsible for approximately 8% of episodes. The main cause of catheter-related candidemia is the ability of some Candida strains-mainly C. albicans and C. parapsilosis-to produce biofilms. Many in vitro and in vivo models have been designed to assess the activity of antifungal drugs against Candida biofilms. Echinocandins have proven to be the most active antifungal drugs. Potential options in situations where the catheter cannot be removed include the combination of systemic and lock antifungal therapy. However, well-designed and -executed clinical trials must be performed before firm recommendations can be issued.